A terrible thing to waste : environmental racism and its assault on the American mind - Washington, Harriet A (Little, Brown Spark, 2019)
Did you know... Middle-class African American households with incomes between $50,000 and $60,000 live in neighborhoods that are more polluted than those of very poor white households with incomes below $10,000. When swallowed, a lead-paint chip no larger than a fingernail can send a toddler into a coma -- one-tenth of that amount will lower his IQ. Nearly two of every five African American homes in Baltimore are plagued by lead-based paint. Almost all of the 37,500 Baltimore children who suffered lead poisoning between 2003 and 2015 were African American. From injuries caused by lead poisoning to the devastating effects of atmospheric pollution, infectious disease, and industrial waste, Americans of color are harmed by environmental hazards in staggeringly disproportionate numbers. This systemic onslaught of toxic exposure and institutional negligence causes irreparable physical harm to millions of people across the country-cutting lives tragically short and needlessly burdening our health care system. But these deadly environments create another insidious and often overlooked consequence: robbing communities of color, and America as a whole, of intellectual power.